Regulatory popular initiative in favor of priority care groups in the canton of Portoviejo, Ecuador - Alava Bravo, Yomayra (2025)
The objective of this study was to analyze normative popular initiatives as a tool for formulating cantonal ordinances that benefit priority attention groups in Portoviejo, Ecuador. The research is justified by the need to reduce inequalities through inclusive and participatory public policies aligned with the Sustainable Development Goals. A qualitative approach was used, involving documentary review, ordinance analysis, and interviews with key actors from the Decentralized Autonomous Government (GAD). The interviews explored citizen participation, limitations in ordinance creation, and their impact on public policies. The results revealed that, while relevant ordinances exist for priority attention groups and vulnerable populations, such as older adults and people with disabilities, their implementation faces significant challenges. These include a lack of financing mechanisms, ineffective monitoring, and limited citizen participation, especially in rural areas. It is concluded that strengthening the dissemination of participation mechanisms, ensuring adequate funding, and establishing technical monitoring processes are essential to maximize the impact of public policies. Furthermore, the study highlights the need to integrate intersectional approaches into ordinances to address multiple vulnerabilities simultaneously, thereby promoting more inclusive and sustainable local governance.